ANALYSIS OF HEAVY METAL CONTENT IN WATER, SEDIMENT, AND FISH IN THE WATERS OF DUMAI CITY, RIAU PROVINCE - Djunaidi, Djunaidi; Arkham, Muhammad Nur; Hutapea, Roma Yuli F.; Kelana, Perdana Putra; Ikhsan, Suci Asrina; Haris, Rangga Bayu Kusuma; Widagdo, Aris; Sari, Iya Purnama; Rejeki, Sri Untari Puji; Sumitro, Martinus Robinson (Jurnal Segara, 2025)
The waters of Dumai City, located in Riau Province and directly connected to the Malacca Strait, are highly accessible both locally and internationally. The coastal area is characterized by intensive human settlements and diverse industrial activities, including oil and gas, crude palm oil (CPO), and cement industries, which discharge wastes that may affect marine biota. Most of these wastes are transported to the sea through river flows, posing a serious threat to the ecological balance and aquatic organisms, particularly fish, with potential risks to human consumers. This study aimed to examine the physicochemical parameters of the waters and to determine the concentration and status of cadmium (Cd) and lead (Pb) in water, sediment, and fish. The research was conducted from April to June 2025 using survey, observation, and experimental methods in both field and laboratory settings. Data were analyzed using Atomic Absorption Spectrophotometry (AAS) to measure the actual concentrations of heavy metals. The results were compared with the threshold values established by the Indonesian Ministry of Environment Decree No. 51/2004 concerning marine water quality standards for aquatic biota. The findings revealed that the physicochemical parameters, including water temperature, salinity, and dissolved oxygen (DO), remain supportive of aquatic life according to the standards. However, the concentrations of Pb and Cd in water, sediment, and fish samples exceeded the permissible limits, indicating pollution in Dumai waters.